Development of multi-systems for measurement of radionuclide absolute activity (Brazilian Journal of Radiation Sciences, 2021)
The development of a multi-systems triple-to-double coincidence ratio (TDCR) and coincidence 4pb-g methods, based on liquid scintillation to radionuclide standardization is presented in this work. The adjustments of multi-systems were made using standards of 3H and 14C and 60Co. The initial stage was performing measurements of pure beta-emitters 3H, 63Ni, and 90Sr90Y standard solutions by TDCR.  The results were consistent within the standard uncertainty. Measurements will be performed with a beta-gamma 60Co in a comparison to the SIR / BIPM to assess the multi-system's performance.